Satisfaction with life and its determinants in the group of patients with ulcerative colitis - Kózka, Maria; Skowron, Wioletta (Nursing in the 21st Century, 2019)
SATISFACTION WITH LIFE AND ITS DETERMINANTS IN THE GROUP OF PATIENTS WITH ULCERATIVE COLITIS Introduction. Satisfaction with life and its determinants are components of human well-being, which the individual assesses in the area of quality of life, based on the own adopted criteria. Of particular interest is the recognition of these factors in people who are struggling with chronic diseases such as ulcerative colitis. Aim. The aim of the work was to get to know the level of life satisfaction as well as its determinants such as acceptance of the disease and generalized self-efficacy of patients with ulcerative colitis. Material and methods. The prospective study included 102 patients with diagnosed ulcerative colitis, who were tested for the level of life satisfaction and the level of disease acceptance and generalized self-efficacy. Descriptive statistics, parametric and nonparametric tests were used for data analysis. Correlation analyzes for variables expressed in ordinal scales were made using r-Pearson correlation. Significance was assumed at the level of p <0.05. Results. The level of life satisfaction, acceptance of the disease and generalized self-efficacy in the subjects were reduced. The level of life satisfaction was dependent on the level of self-efficacy and acceptance of the disease. The level of life satisfaction of the respondents correlated with the generalized own effectiveness and acceptance of the disease. A higher level of life satisfaction was obtained by respondents with a higher level of disease acceptance and convinced of effective coping with difficult situations. Men presented better results than women. Conclusions. Satisfaction with life and its determinants in patients with ulcerative colitis were reduced. The respondents with vocational education achieved lower results than those with secondary and higher education. Women presented lower variable levels than men. The level of satisfaction was dependent on the acceptance of the disease and on the generalized own effectiveness.